Herbal medicinal product Sinupret extract (BNO 1016) is safe and effective in the treatment of acute viral rhinosinusitis - Rainer Jund; Martin Mondigler; Holger Stammer; Pontus Stierna; Claus Bachert (ZAO "Consilium Medicum", 2022)
Aim. The pooled efﬁcacy data of two similar randomized placebo-controlled clinical trials were analyzed. Safety was evaluated on the basis of the individual trials. Materials and methods. The efﬁcacy analysis was based on 589 patients. Treatment was performed orally with either 3160 mg BNO 1016 (n=294) or 31 tablet placebo (n=295) for 15 days. In both trials patients underwent ﬁve visits to the investigational sites. Symptoms were evaluated according to the EPOS 2012 guideline. Ultrasonography was used to conﬁrm the diagnosis at onset of treatment and the remission of symptoms at the last visit. Efﬁcacy was evaluated by the investigator as the mean major symptom score (MSS) at the end of treatment (visit 5, day 14). Patients reported symptoms and social/emotional consequences of rhinosinusitis using a quality of life questionnaire (SNOT-20 GAV). Results. MSS improved during the treatment period by a mean of 10.021.61 score points to 2.472.55 for BNO 1016 and of 9.871.52 to 3.633.63 for placebo. Differences between treatment groups at end of therapy (1.163.14 score points; p0.0001) and patient-assessed quality of life (p=0.0015) were statistically signiﬁcant in favor of BNO 1016. Conclusion. Daily intake of 480 mg of BNO 1016 for 15 days is an effective treatment in acute viral rhinosinusitis.